Updating youth programming to meet needs of urban schools - Rebecca McMahon (Urban Food Systems Symposium, 2020)
Sedgwick County, Kansas is home to the largest school district in the state of Kansas, USD 259-Wichita Public Schools. The county is also home to several suburban and rural school districts. Because of the urban-rural continuum present in the county, many students have very little experience with hands on plant science, gardening, or agriculture while other students are exposed to those concepts daily. K-State Research & Extension - Sedgwick County Master Gardener volunteers have been providing 4-H plant science school enrichment lessons for over 15 years as a way to engage the next generation in plant science, gardening and agriculture. These lessons were popular with teachers and volunteers, but the lessons did not meet the new Common Core / Next Generation Science Standards. Over a period of three years, requests by teachers had dropped by half. Also, teaching methods of the volunteers did not meet the expectations of modern students and teachers for hands-on and interactive learning. At the same time, interest in school gardens and school gardening programs has increased in our urban schools, but the programs were not prepared to meet that need for programming. Navigating the process of updating the lesson plans to meet the needs of urban schools, matching up with the science standards, improving hands-on learning, enriching the exposure of students to plant science, and engaging passionate volunteers in program delivery was long and difficult, but shows signs of good results.
Keywords: plant science; education; volunteers; gardening; science standards; hands-on learning